Examining Self-Determination Theory in the Context of Higher Education and Distance Education - Sanal, Seda Ozer; Torun, Fulya; Guler, Tulay Dargut (Int Soc Technology Education & Science-Istes, 2025)
Self-determination theory (SDT) offers a conceptual framework and practice for more successful and highly motivated university students in distance education. In the context of distance education, SDT has been examined from the perspective of students, academicians and system administrators. In this study, it is aimed to evaluate the distance education processes of university students within the scope of SDT, to determine the current situation and to obtain suggestions for high success and motivation. In the study conducted in a phenomenological framework, the questions What is being done? and What can be done? were answered by university students, academics and system administrators regarding the dimensions of autonomy, competence and relatedness. 89 university students, 17 academicians and 12 system administrators were interviewed and inductive analysis was performed. As a result of the analysis, stakeholder views on how autonomy, competence and relatedness needs are met and how they can be met are given in themes and sub-themes. In addition to the findings supported by the literature, new findings are also noteworthy. Implications for future higher education, distance education and SDT research and practice are discussed.
Keywords: Higher education; Distance education; Self determination Theory; Qualitative research